Additional records of cicadas (Hemiptera: Cicadidae) to the fauna of Mindanao, Philippines, with the description of three new species and a key to the species of Champaka Distant - Lee, Young June (Zootaxa, 2015)
This paper provides the revised checklist of the tribes, subtribes, genera, and species of the family Cicadidae from Mindanao, Philippines, comprising 22 species belonging to 16 genera. Three new species, Champaka solivenae sp. nov., Purana crassinotata sp. nov., and Ggomapsalta fragilis sp. nov., are described. Lembeja fatiloqua (Stål, 1870) is added to the list, which was omitted in the previous checklist. Neoncotympana leeseungmoi Lee, 2011 is added to the list, which was described after the previous checklist. Oncotympana averta Lee, 2011 is newly recorded from Mindanao, replacing Oncotympana sp. listed in the previous checklist. A key to the 12 species of Champaka Distant, 1905 is provided.